Clinico-Etiological Profile of Goitrous Children of a Coastal Area and the Association Between Urinary Iodine Concentration and Thyroid Autoimmunity - Greeshmendu Rajan; P R Sreelatha; R V Chinchilu; E S Gilsa (National Board of Examinations Journal of Medical Sciences)
Background: Iodine deficiency is unlikely to be a main cause of goitre in a coastal area, with a predominant sea food eating population. At the same time, excess iodine may cause thyroid autoimmunity and hypothyroidism via the Wolff-Chaikoff effect. Measurement of Urinary Iodine Concentration (UIC) per day is an excellent substitute for assessing the iodine intake. The objectives of this study are to describe the clinico-etiological profile and to determine the correlation between Urinary Iodine Concentration and thyroid autoimmunity in goitrous children below 12 years of age attending a tertiary care institute in a coastal area. Materials & Methods: It was a cross-sectional analytical study in a coastal tertiary care institute. Children attending the department of Pediatrics were screened for goitre. UIC and thyroid autoimmunity were ascertained using standard techniques. Results: Nearly 1/3rd of goitrous children had thyroid autoimmunity. The median Urinary Iodine Concentration (UIC) of the study area was 210 μ/L, which is above adequate level, as per WHO grading. Conclusion: Thyroid autoimmunity is an important cause for goiter in children from this coastal area and a high iodine intake may be contributing to this. Hence, the salt iodization in coastal areas may need a reconsideration. However, further community-based studies may help to provide an epidemiological level of recommendation regarding the iodine supplementation (salt iodization) in coastal areas.